Ceza muhakemesinde delillerin doğrudan doğruyalığı ilkesi - Turgut, Bahar (My University, 2024)
Ceza muhakemesinin amacı maddi gerçeğin araştırılması ve elde edilen maddi gerçeğe dayanarak adaletin sağlanmasıdır. Bu amaca ulaşmak için hareket eden muhakeme süjelerinin uyması gereken bazı ilkeler vardır. Bu ilkelerin en önemlilerinden birisi delillerin doğrudan doğruyalığı ilkesidir. Bu ilke gereğince yargılama makamı, duruşmada beş duyu organı ile incelediği, tartışmaya açtığı ve değerlendirdiği delilleri hükme esas almalıdır. Ceza muhakemesinin doğru bir şekilde ilerleyebilmesi için delillerin doğrudan doğruyalığı ilkesinin kavramsal olarak açıklanması, tarihsel gelişim sürecinin, kapsam ve sonuçlarının belirlenmesi, ilkeye yöneltilen eleştirilerin tartışılması ve böylece ceza muhakemesi uygulamasında delillerin doğrudan doğruyalığı ilkesinin uygulanmasıyla ilgili olarak ortaya çıkan eksiklik ve yanlış uygulamaların tespit edilmesi gerekmektedir. Ayrıca delillerin doğrudan doğruyalığı ilkesinin istisnaları belirlenerek bu istisnaların kabul ediliş gerekçeleri açıklanmalıdır. Kanun koyucunun delillerin doğrudan doğruyalığı ilkesine istisna getirmesinin gerekçeleri araştırılarak bu gerekçelere uygun sonuçlara ulaşılıp ulaşılmadığı ve dolaylı delil ikamesinin mümkün olup olmadığı tespit edilmelidir. Bu tespitlerin yapılabilmesi için yeri geldikçe Yargıtay, Anayasa Mahkemesi ve Avrupa İnsan Hakları Mahkemesi’nin kararlarından elde edilen veriler kullanılarak delillerin doğrudan doğruyalığı ilkesinin daha doğru bir şekilde uygulanmasına yönelik öneriler ortaya konulmalıdır.

The purpose of criminal procedure is to investigate the material truth and to ensure justice based on the material truth obtained. There are certain principles that subjects of reasoning must comply with when acting to achieve this goal. One of the most important of these principles is the principle of directness of evidence. In accordance with this principle, the judging authority should base its decision on accessible evidence that it examines with five senses and discusses with the five senses at the hearing. The main purpose of this study is to conceptually explain the principle of directness of evidence, determine its historical development, scope and consequences, discuss the criticisms directed to the principle, and thus identify the deficiencies and wrong practices that arise regarding the application of the principle of directness of evidence in criminal procedure practice. For this purpose, when appropriate, the decisions of the Supreme Court, the Constitutional Court and the European Court of Human Rights will be examined and the findings of the relevant courts will also be taken into account. It is aimed to put forward suggestions for a more accurate application of the principle of directness of evidence by using the data obtained through these determinations. The thesis also aims to explain the reasons for accepting these exceptions by including exceptions to the principle of directness of evidence. For this purpose, it will be investigated whether it is possible to substitute indirect evidence. The aim is to investigate the reasons why the legislator made an exception to the principle of directness of evidence and to determine whether results in line with these reasons have been reached.
The principle of directness of evidence in criminal procedure
Keywords: Adil yargılanma; adil yargılanma hakkı; delil değerlendirmesi; delil ikamesi; Delillerin doğrudan doğruyalığı ilkesi; evaluation of evidence; Fair trial; Principle of directness of evidence; right to a fair trial; substitution of evidence; trial authority; Turkey; Türkiye; yargılama makamı